The role of vitamins K and D in the processes of ectopic calcification in patients with chronic kidney disease: The current state of the problem - Susla, O.; Bushtynska, O.; Danyliv, S.; Logoyda, L.; Gozhenko, A. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Abstract. The generalization of experimental and clinical data currently allows us to confirm the important pathogenetic role of vitamin K deficiency in cardiovascular calcification and atherosclerotic damage in chronic kidney disease (CKD). It was highlighted that, apart from vitamin K, the activity and expression of matrix Gla protein, which strongly inhibits vascular calcification, depended to a considerable extent on vitamin D. The efficacy and safety of the combined intake of vitamin K and D in slowing the progression of ectopic calcification, reducing cardiovascular risk, and improving prognosis in CKD patients need to be confirmed in multicenter randomized controlled trials.